2009
DOI: 10.1021/ie801572w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodisperse Glycerol Dimethacrylate-Based Microgel Particles by Precipitation Polymerization

Abstract: A new, single-stage precipitation polymerization was proposed for the synthesis of monodisperse crosslinked glycerol dimethacrylate (GDMA)-based microgel particles carrying hydroxyl and carboxyl functionalities, from nanometer to micrometer size range. The synthesis of monodisperse microgel spheres in the size range of 30-1500 nm was possible by the proposed method. In the polymerizations, glycerol dimethacrylate was copolymerized with methacrylic acid (MAA) in the medium containing toluene and acetonitrile wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…It should be noted that commercial DVB is technical, composed of either 55% or 80% DVB with the rest being mostly ethyl styrene monomer. Methacrylate crosslinkers are also polymerized via precipitation polymerization with a low percentage of added monomer [50][51]. As a result, precipitation polymerized particles are rich in remaining double bonds that can be efficiently utilized in post-functionalization [52] (see further functionalization section).…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that commercial DVB is technical, composed of either 55% or 80% DVB with the rest being mostly ethyl styrene monomer. Methacrylate crosslinkers are also polymerized via precipitation polymerization with a low percentage of added monomer [50][51]. As a result, precipitation polymerized particles are rich in remaining double bonds that can be efficiently utilized in post-functionalization [52] (see further functionalization section).…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…As a result of the fact that the nuclei do not overlap, highly monodisperse particles, generally in the size range of 1-5 µm, are obtained [54]. Recently, monodisperse nanoparticles are also reported [50]. As one of the unique properties of this technique, particles grow constantly and the polymerization can be stopped when the desired particle size is reached.…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Saracoglu et al [26] reported that monodisperse cross-linked poly(glycerol dimethacrylate) (poly(GDMA))-based microgel particles carrying hydroxyl and carboxyl functionalities from nanometer to micrometer size range were synthesized by single-stage precipitation polymerization. The authors claimed that the produced poly (GDMA) microbeads could be used widely as a promis-ing material for biotechnological and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, like in seeded suspension polymerization the obtained beads are in the range of 0.1-10 micrometer, which is not suitable for solid phase synthesis and catalysis applications due to handling problems. Also, the incorporation of functional monomers can be problematic or impossible 29 , because of the delicate mechanism of growing polymer chain precipitation during the polymerization.…”
Section: Introductionmentioning
confidence: 99%